Improving the Competency of the Elderly in Reading the AlÂ¬Quran Through the 'Asyarah Method After Covid 19 Pandemic - Febriyarni, Busra; Nurjannah, Nurjannah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
During the February 2020 Covid-19 pandemic, the regional government attempted to implement Large-Scale Social Restrictions (PSBB), as a result, people began to experience difficulties in carrying out economic activities. Worship, transportation and others. This is also felt by the elderly mothers of Aisyiyah Rejang Lebong who have been actively studying tahsin tahfizh. The focus of this research is to look at increasing the competence of the elderly in studying the Koran using the Tahsin 'Asyarah method for the elderly mothers of Aisyiyah Rejang Lebong with the hope that they will be fluent in reading the Koran as a preparation for the eternal village. PAR is the method used in this research. The research subjects were community members who were members of the Aisyiyah Elderly recitation and they participated in the design, implementation and execution of the research. In PAR theory, there is a cycle that is used as a benchmark for the success of a research process based on community empowerment. Namely KUPAR (to Know, to Understand, to Plan, to Action and to Reflection. The research results show that this method is very suitable for the elderly so that they can easily learn tahsin and memorize the Al-Quran. This is proven that during the assisted program the mothers have memorized it several selected surahs, namely al-Mulk, al-Kahfi 1-10, Arrahman, al-Waqiah and al-Baqarah 1-40. This 'Asyarah method enables elderly Aisyiyah mothers to become good at reading according to the science of recitation in a relatively short time for 2 months.